Ionic liquids as a tool for lignocellulosic biomass fractionation - Lopes, André (2014)
Lignocellulosic biomass composes a diversity of feedstock raw materials representing an abundant and renewable carbon source. In majority lignocellulose is constituted by carbohydrate macromolecules, namely cellulose and hemicellulose, and by lignin, a polyphenilpropanoid macromolecule. Between these biomacromolecules, there are several covalent and non-covalent interactions defining an intricate, complex and rigid structure of lignocellulose. The deconstruction of the lignocellulosic biomass makes these fractions susceptible for easier transformation to large number of commodities including energy, chemicals and material within the concept of biorefinery. Generally, the biomass pre-treatment depends on the final goal in the biomass processing. The recalcitrance of lignocellulose materials is the main limitation of its processing once the inherent costs are excessively high for the conventional pre-treatments. Furthermore, none of the currently known processes is highly selective and efficient for the satisfactory and versatile use, thus, new methodologies are still studied broadly. The ionic liquid technology on biomass processing is relatively recent and first studies were focused on the lignocellulosic biomass dissolution in different ionic liquids (ILs). The dissolution in IL drives to the structural changes in the regenerated biomass by reduction of cellulose crystallinity and lignin content contrasting to the original biomass. These findings provided ILs as tools to perform biomass pre-treatment and the advantageous use of their specific properties over the conventional pre-treatment processes. This review shows the critical outlook on the study of biomass dissolution and changes occurred in the biomass during this process as well as on the influence of several crucial parameters that govern the dissolution and further pre-treatment process. The review of currently known methods of biomass fractionation in IL and aqueous-IL mixtures is also discussed here and perspectives regarding these topics are given as well.